Attentional bias toward health-threat in health anxiety: a systematic review and three-level meta-analysis. Issue 4 (10th March 2022) - Shi, Congrong; Taylor, Steven; Witthöft, Michael; Du, Xiayu; Zhang, Tao; Lu, Shan; Ren, Zhihong
Abstract: Attentional bias toward health-threat may theoretically contribute to the development and maintenance of health anxiety, but the empirical findings have been controversial. This study aimed to synthesize and explore the heterogeneity in a health-threat related attentional bias of health-anxious individuals, and to determine the theoretical model that better represents the pattern of attentional bias in health anxiety. Four databases (Web of Science, PubMed, PsycINFO, and Scopus) were searched for relevant studies, with 17 articles ( N = 1546) included for a qualitative review and 16 articles (18 studies) for a three-level meta-analysis ( N = 1490). The meta-analytic results indicated that the health anxiety group, compared to the control group, showed significantly greater attentional bias toward health-threat ( g = 0.256). Further analyses revealed that attentional bias type, paradigm, and stimuli type were significant moderators. Additionally, compared to the controls, health-anxious individuals displayed significantly greater attention maintenance ( g = 0.327) but nonsignificant attention vigilance to health-threat ( g = −0.116). Our results provide evidence for the attention maintenance model in health-anxious individuals. The implications for further research and treatment of elevated health anxiety in the context of coronavirus disease-2019 (COVID-19) were also discussed.